2020
DOI: 10.1002/anie.202009490
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Neutral TEMPO Catalysis: Direct Radical (Hetero)Aryl C−H Di‐ and Trifluoromethoxylation

Abstract: Applications of TEMPOC catalysis for the development of redox-neutral transformations are rare. Reported here is the first TEMPOC-catalyzed, redox-neutral CÀH di-and trifluoromethoxylation of (hetero)arenes. The reaction exhibits a broad substrate scope, has high functional-group tolerance, and can be employed for the late-stage functionalization of complex druglike molecules. Kinetic measurements, isolation and resubjection of catalytic intermediates, UV/Vis studies, and DFT calculations support the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…Initially, ( n -Bu 4 N + ) 2 S 2 O 8 2– suffers an homolytic cleavage to afford two equivalents of the oxygen-centered radical • SO 4 – ( n -Bu 4 N + ). These radicals subsequently participate in two process: (a) the generation of species I via the SET process from adduct 19 and (b) the oxidation of TEMPO 21 to species A [TEMPO + ]­SO 4 2– ( n -Bu 4 N + ) . After intramolecular 5- endo -trig radical cyclization onto the N -benzoyl moiety, transient cyclohexanedienyl radical species II is oxidized to cation III by the effect of the strong oxidant oxoammonium salt A .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Initially, ( n -Bu 4 N + ) 2 S 2 O 8 2– suffers an homolytic cleavage to afford two equivalents of the oxygen-centered radical • SO 4 – ( n -Bu 4 N + ). These radicals subsequently participate in two process: (a) the generation of species I via the SET process from adduct 19 and (b) the oxidation of TEMPO 21 to species A [TEMPO + ]­SO 4 2– ( n -Bu 4 N + ) . After intramolecular 5- endo -trig radical cyclization onto the N -benzoyl moiety, transient cyclohexanedienyl radical species II is oxidized to cation III by the effect of the strong oxidant oxoammonium salt A .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Having developed a set of efficient photocatalytic conditions, we next sought to investigate alternative approaches for activating BTMP, which do not require light irradiation. While initial results had identified metal salts such as CuCl as suitable stoichiometric activators, we were drawn to the recent report from Ngai and co‐workers using catalytic amounts of (2,2,6,6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO) as a single electron shuttle with reagent C [6c] . TEMPO is significantly less expensive than [Ru(bpy) 3 ][PF 6 ] 2 while the avoidance of light irradiation brings practical advantages for potential large scale applications [12] .…”
Section: Methodsmentioning
confidence: 99%
“…226 In 2020, Liu and Ngai et al reported the TEMPO-catalyzed redox-neutral C-H di-and trifluoromethoxylation of (hetero)arenes. 227 The principle of the reaction was similar to the NFSI-mediated amination reaction.…”
Section: -7-1 Oxidation Of Organosulfur Compoundsmentioning
confidence: 99%